Occurrence of simple sequence repeats in cDNA sequences of safflower (Carthamus tinctorius) reveals the importance of SSR-containing genes for cell biology and dynamic response to environmental cues - Ahmadi, Ahmad Jawid; Ahmadikhah, Assadollah (Frontiers in Plant Science, 2022)
Safflower (Carthamus tinctorius) is a diploid crop plant belonging to the family Asteraceae and is well known as one of important oilseed crops due to edible oil containing unsaturated fatty acids. In recent years it is gaining increased attention for food, pharmaceutical and industrial uses, and hence the updating its breeding methods is necessary. Genic simple sequence repeats (SSRs) in addition of being desire molecular markers, are supposed to influence gene function and the respective phenotype. This study aimed to identify SSRs in cDNA sequences and further analysis of the functional features of the SSR-containing genes to elucidate their role in biological and cellular processes. We identified 1,841 SSR regions in 1,667 cDNA sequences. Among all types of repeats, trinucleotide repeats were the most abundant (35.7%), followed by hexanucleotide (29.6%) and dinucleotide repeats (22.0%). Thirty five SSR primer pairs were validated by PCR reaction, detected a high rate of polymorphism (>57%) among safflower accessions, physically mapped on safflower genome and could clearly discriminate the cultivated accessions from wild relatives. The cDNA-derived SSR markers are suitable for evaluation of genetic diversity, linkage and association mapping studies and genome-based breeding programmes. Occurrence of SSR repeats in biologically-important classes of proteins such as kinases, transferases and transcription factors was inferred from functional analyses, which along with variability of their repeat copies, can endow the cell and whole organism the flexibility of facing with continuously changing environment, and indicate a structure-based evolution mechanism of the genome which acts as an up-to-dating tool for the cell and whole origanism, which is realized in GO terms such as involvement of most SSR-containing genes in biological, cellular and metabolic processes, especially in response to stimulus, response to stress, interaction to other organisms and defense responses.